Metal-free one-pot domino synthesis of oxazolidinethione derivatives of quaternary amino acids from α-amino esters and aldehydes using CS2 - Shinde, Dinesh R.; Krishna, Gamidi Rama; Marelli, Udaya Kiran (Journal of Organic Chemistry, 2024)
We present a streamlined, metal-free, one-pot domino approach to efficiently synthesize oxazolidinethione derivatives containing substituted quaternary amino acids. This method employs alpha-amino esters, aldehydes, and CS2 under mild conditions, constructing three new bonds (C-N, C-C, and C-O) to produce oxazolidinethione compounds featuring a quaternary center and a beta-hydroxy derivative in high yields. This scalable protocol enables the creation of libraries of biologically significant, intricate amino acid derivatives using amino esters and aldehydes.